Indigenous Scholarship, en français SVP! - ALLARD-TREMBLAY, YANN; CHOQUETTE, ÉLÉNA; GREEN, JOYCE; STARBLANKET, GINA; MAJOR, REBECCA; ZÚÑIGA, DIDIER (Journal of Canadian Studies, 2026)
Today, there is a vast and important Indigenous studies and decolonial literature available in English. In French, Indigenous studies and cognate literature is considerably smaller. We consider some of the reasons for this state of affairs. They include the minoritized role of French across Canadian academia and the significant under-representation of Indigenous faculty in French-language academic institutions. Consequently, French-language materials about Indigenous peoples and politics are primarily authored by non-Indigenous scholars. This raises important questions about what "Indigenous studies" and "decolonizing literature" mean in Francophone academic writing. We discuss the consequences for the settler academy today, taking up the limited scope of Indigenous literature in French and the problem this represents for Indigenous and non-Indigenous student cohorts, as well as for the field of Indigenous studies. The discussion considers practices that we can take in our classrooms, our universities, and within our association and affiliated journal to better support Indigenous authorship, including in the French language.